2020
DOI: 10.1089/jayao.2019.0157
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Features of Psychosocial Distress of Adolescents and Young Adults with Cancer Compared to Adults at Diagnosis: Patient-Reported Domains of Concern

Abstract: Purpose: Adolescents and young adults (AYA) (18-40) are a population of patients with cancer, who have distinctive developmental and psychosocial pressures. Using validated distress screening tools, we investigated psychosocial needs of AYA compared to older adults with cancer at diagnosis. Methods: AYA and older adult patients from British Columbia, Canada, between 2011 and 2016, who completed the Canadian Problem Checklist (CPC) and the PsychoSocial Screen for Cancer-Revised (PSSCAN-R) within 6 months of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 20 publications
(36 reference statements)
0
10
2
Order By: Relevance
“…Our finding of gender differences in anxiety but not in depression only partially corroborates a previous study that reported gender differences in mental health ( De Girolamo et al, 2006 ), and conflicts with previous studies that reported higher depressive states in females than males ( Linden et al, 2012 ; Muzzatti et al, 2018 ). Younger participants in this study had less anxiety and depression than older patients, in accordance with one previous study ( Sellick and Edwardson, 2007 ) but conflicting with other studies that found either higher depression and anxiety in younger patients ( Linden et al, 2012 ; Naik et al, 2020 ; Smrke et al, 2020 ) or no age-related differences ( Annunziata et al, 2012 ). For instance, the prevalence of moderate (26 vs. 20%) and severe (27 vs. 17%) distress was higher in 18–40-year-old cancer patients within 6 months of their diagnosis than in older patients ( Smrke et al, 2020 ).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Our finding of gender differences in anxiety but not in depression only partially corroborates a previous study that reported gender differences in mental health ( De Girolamo et al, 2006 ), and conflicts with previous studies that reported higher depressive states in females than males ( Linden et al, 2012 ; Muzzatti et al, 2018 ). Younger participants in this study had less anxiety and depression than older patients, in accordance with one previous study ( Sellick and Edwardson, 2007 ) but conflicting with other studies that found either higher depression and anxiety in younger patients ( Linden et al, 2012 ; Naik et al, 2020 ; Smrke et al, 2020 ) or no age-related differences ( Annunziata et al, 2012 ). For instance, the prevalence of moderate (26 vs. 20%) and severe (27 vs. 17%) distress was higher in 18–40-year-old cancer patients within 6 months of their diagnosis than in older patients ( Smrke et al, 2020 ).…”
Section: Discussioncontrasting
confidence: 54%
“…Younger participants in this study had less anxiety and depression than older patients, in accordance with one previous study ( Sellick and Edwardson, 2007 ) but conflicting with other studies that found either higher depression and anxiety in younger patients ( Linden et al, 2012 ; Naik et al, 2020 ; Smrke et al, 2020 ) or no age-related differences ( Annunziata et al, 2012 ). For instance, the prevalence of moderate (26 vs. 20%) and severe (27 vs. 17%) distress was higher in 18–40-year-old cancer patients within 6 months of their diagnosis than in older patients ( Smrke et al, 2020 ). Burgoyne et al (2015) compared the distress levels of cancer patients aged 18–39, 40–64, and 65–90 years, and found that the youngest group had higher cancer-related distress than the oldest one but similar distress levels to the middle-aged group.…”
Section: Discussioncontrasting
confidence: 54%
“…First and foremost, our results highlighted the central role of developmental distress since consistent results were found in its centrality and its interplay with QoL in three networks. A Canadian study found that most concerns reported by AYAs fall into practical areas such as work/school and finances 24 . The consensus is that AYAs all belong to a specific age group with the life purpose of independence and development.…”
Section: Discussionmentioning
confidence: 99%
“…We recommend that pediatric and AYA patients receive regular, ongoing psychosocial screening and that AYA patients are given the opportunity for care planning away from caregivers to promote privacy. Screening and assessment should include areas specific to the unique stressors of the AYA population, such as the following domains: emotional, physical, spiritual, social (peers, family, romantic), practical (education, career development, employment), and informational (fertility and healthy lifestyle behaviors—safe sex and tobacco, alcohol, and substance abuse) 93 …”
Section: Individual Characteristicsmentioning
confidence: 99%
“…Screening and assessment should include areas specific to the unique stressors of the AYA population, such as the following domains: emotional, physical, spiritual, social (peers, family, romantic), practical (education, career development, employment), and informational (fertility and healthy lifestyle behaviors-safe sex and tobacco, alcohol, and substance abuse). 93…”
Section: Recommendationsmentioning
confidence: 99%